Episodes of strain experienced in the operating room: impact of the type of surgery, the profession and the phase of the operation - Sandra Keller; Steven Yule; Douglas S. Smink; Vivian Zagarese; Shawn Safford; Sarah Henrickson Parker (BMC Surgery, 2020)
Abstract Background Strain episodes, defined as phases of higher workload, stress or negative emotions, occur everyday in the operating room (OR). Accurate knowledge of when strain is most intense for the different OR team members is imperative for developing appropriate interventions. The primary goal of the study was to investigate temporal patterns of strain across surgical phases for different professionals working in the OR, for different types of operations. Methods We developed a guided recall method to assess the experience of strain from the perspective of operating room (OR) team members. The guided recall was completed by surgeons, residents, anesthesiologists, circulating nurses and scrub technicians immediately after 113 operations, performed in 5 departments of one hospital in North America. We also conducted interviews with 16 surgeons on strain moments during their specific operation types. Strain experiences were related to surgical phases and compared across different operation types separately for each profession in the OR. Results We analyzed 693 guided recalls. General linear modeling (GLM) showed that strain varied across the phases of the operations (defined as before incision, first third, middle third and last third) [quadratic (F = 47.85, p < 0.001) and cubic (F = 8.94, p = 0.003) effects]. Phases of operations varied across professional groups [linear (F = 4.14, p = 0.001) and quadratic (F = 14.28, p < 0.001) effects] and surgery types [only cubic effects (F = 4.92, p = 0.001)]. Overall strain was similar across surgery types (F = 1.27, p = 0.28). Surgeons reported generally more strain episodes during the first and second third of the operations; except in vascular operations, where no phase was associated with significantly higher strain levels, and emergency/trauma surgery, where strain episodes occurred primarily during the first third of the operation. Other professional groups showed different strain time patterns. Conclusions Members of the OR teams experience strain differently across the phases of an operation. Thus, phases with high concentration requirements may highly vary across OR team members and no single phase of an operation can be defined as a “sterile cockpit” phase for all team members.